Miocene Diversification in the Savannahs Precedes Tetraploid Rainforest Radiation in the African Tree Genus Afzelia (Detarioideae, Fabaceae) - Donkpegan, Armel S. L.; Doucet, Jean-Louis; Hardy, Olivier J.; Heuertz, Myriam; Piñeiro, Rosalía (Frontiers in Plant Science, 2020)
The dating of diversification events, including transitions between biomes, is key to elucidate the processes that underlie the assembly and evolution of tropical biodiversity. Afzelia is a widespread genus of tropical trees, threatened by exploitation for its valuable timber, that presents an interesting system to investigate diversification events in Africa. Africa hosts diploid Afzelia species in the savannahs north and south of the Guineo-Congolian rainforest and autotetraploid species confined to the rainforest. Species delimitation and phylogenetic relationships among the diploid and tetraploid species remained unresolved in previous studies using small amounts of DNA sequence data. We used genotyping-by-sequencing in the five widespread Afzelia species in Africa, the savannah species A. africana and A. quanzensis and the rainforest species A. bipindensis, A. pachyloba and A. bella. Maximum likelihood and coalescent approaches resolved all species as monophyletic and placed the savannah and rainforest taxa into two separate clades corresponding to contrasted ploidy levels. Our data are thus compatible with a single biome shift in Afzelia in Africa, although we were unable to conclude on its direction. SNAPP calibrated species trees show that the savannah diploids started to diversify early, at 9.36 (0.08-20.36) Ma, which contrasts with a recent and rapid diversification of the rainforest tetraploid clade, starting at 2.92 (0.03 - 6.37) Ma. This finding of older diversification in a tropical savannah clade vs. its sister rainforest clade is exceptional; it stands in opposition to the predominant observation of young ages for savannahs lineages in tropical regions during the relatively recent expansion of the savannah biome.